Top Market Strategy: Applying the 80/20 Rule - Kruger, Elizabeth Rush (Business Expert Press, 2011)
Ebook from IG Library ; Virtually every business seeks to increase its profit, but few business leaders realize that a universal law governs profit from customers. You may be applying the 80/20 rule to sales, quality control, investing, or production, without realizing that this rule summarizes the Pareto distribution of inputs to outputs. The 80/20 rule predicts that the top 20% of inputs generate 80% of the outputs, balanced by the bottom 80% of inputs generating 20% of the outputs. Recently mathematicians confirmed that the Pareto distribution is universal and as valid as the normal bell-shaped distribution. This universal law predicts that when customers are segmented by their profitability, the top 20% generate 80% of your profit from customers -- four times more than expected whereas the bottom 80% generate 20% of your profit from customers -- one-fourth as much as expected. This means that customers in your top market segment generate 16 times more profit than customers in your bottom market segment. Hence, when you replace customers in your bottom market segment with new customers in the top market segment, your profit from customers will quadruple. The steps for achieving this amazing result are segmenting your customers by their profitability, distinguishing the top 20% of your customers from others, identifying prospects with these traits, creating a top market strategy, and converting these prospects into highly profitable new customers. The purpose of this book is to show you exactly how to implement a top market strategy in your business, and thereby, achieve the predicted increase in your profit from customers.